Membangun lingkungan sehat : menyambut 50 tahun Indonesia merdeka - Amsyari, Fuad. (Surabaya : Airlangga University Press, 1996)
Environmental management in Indonesia.
Errata slip inserted at end.
Includes bibliographical references (p. 251-253).
Keywords: Environmental management -- Indonesia; Environmental policy -- Indonesia; Indonesia -- Environmental aspects